2016
DOI: 10.1097/md.0000000000002828
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Anxiety in Patients With Myasthenia Gravis and Risk for Myasthenic Crisis After Extended Transsternal Thymectomy

Abstract: A thymectomy can ameliorate the symptoms of myasthenia gravis (MG) and prevent the progression of ocular MG (OMG) to generalized MG (GMG). However, postoperative myasthenic crisis (POMC) is a serious post-thymectomy complication. Preoperative anxiety (POA) is common but typically neglected in MG patients. The association of POA with POMC has not yet been examined.From June 2007 to December 2013, 541 cases of MG were admitted to the First Affiliated Hospital of Sun Yat-sen University (Guangzhou, China). All cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…While plasmapheresis reduced weakness and alleviated physical disability; it had no significant impact on diminishing mood disorders or improving mental HRQoL, suggesting that depression and anxiety may represent emotional responses to the progression of MG associated physical disabilities in the chronic course, that remain intractable throughout the early stage of the physical recovery process [26]. Consistent with this, the retrospective CONSORT study of 541 MG cases in China found a statistically significant, independent association between postoperative myasthenic crises following thymectomies and preoperative anxiety by multivariate linear regression analysis (OR = 2.40; 95% CI: 1.33-4.34; p = 0.004) [27].…”
Section: Effects Of Mg Treatment On Moodmentioning
confidence: 62%
See 1 more Smart Citation
“…While plasmapheresis reduced weakness and alleviated physical disability; it had no significant impact on diminishing mood disorders or improving mental HRQoL, suggesting that depression and anxiety may represent emotional responses to the progression of MG associated physical disabilities in the chronic course, that remain intractable throughout the early stage of the physical recovery process [26]. Consistent with this, the retrospective CONSORT study of 541 MG cases in China found a statistically significant, independent association between postoperative myasthenic crises following thymectomies and preoperative anxiety by multivariate linear regression analysis (OR = 2.40; 95% CI: 1.33-4.34; p = 0.004) [27].…”
Section: Effects Of Mg Treatment On Moodmentioning
confidence: 62%
“…Lack of social support, poor coping mechanisms and acceptance of disease, older age of onset, lower education, occupations associated with increased physical labor, career changes associated with MG, and worsening disease severity are independently statistically significant for associations with diminished HRQoL, which, in turn, can induce emotional stress in individuals afflicted with MG [ 14 , 15 , 27 , 34 - 37 ]. In a cyclical fashion, emotional turmoil can further trigger myasthenic exacerbations, resulting in debilitating physical symptoms [ 15 , 38 ].…”
Section: Reviewmentioning
confidence: 99%
“…The results of the heterogeneity test showed evidence of heterogeneity between studies (I 2 = 67%, P = 0.0006). According to the preoperative Osserman stages, the patients were divided into three subgroups: IIa + IIb + III + VI, IIb + III + VI, and VI + V. The results of the heterogeneity test did not reveal any heterogeneity (I 2 = 0, P > 0.1); therefore, the Preoperative dosage of pyridostigmine bromide Five studies [20,22,28,29,35] including 1103 patients provided data on the relationship between the preoperative pyridostigmine bromide dosage and MCAT. The results of the heterogeneity test showed evidence of heterogeneity between studies (I 2 = 92%, P < 0.00001).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Postoperative risk factors (Fig. 2c) Postoperative lung infection Five studies [8,20,22,33,34] including a total of 989 patients reported the relationship between postoperative lung infection and MCAT. The results of the heterogeneity test showed no evidence of heterogeneity between the studies (I 2 = 0%, P = 0.45); therefore, the fixed effect model was used for the analysis.…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation